If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 1)(x + 2) = -1 Reorder the terms: (1 + 5x)(x + 2) = -1 Reorder the terms: (1 + 5x)(2 + x) = -1 Multiply (1 + 5x) * (2 + x) (1(2 + x) + 5x * (2 + x)) = -1 ((2 * 1 + x * 1) + 5x * (2 + x)) = -1 ((2 + 1x) + 5x * (2 + x)) = -1 (2 + 1x + (2 * 5x + x * 5x)) = -1 (2 + 1x + (10x + 5x2)) = -1 Combine like terms: 1x + 10x = 11x (2 + 11x + 5x2) = -1 Solving 2 + 11x + 5x2 = -1 Solving for variable 'x'. Reorder the terms: 2 + 1 + 11x + 5x2 = -1 + 1 Combine like terms: 2 + 1 = 3 3 + 11x + 5x2 = -1 + 1 Combine like terms: -1 + 1 = 0 3 + 11x + 5x2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. 0.6 + 2.2x + x2 = 0 Move the constant term to the right: Add '-0.6' to each side of the equation. 0.6 + 2.2x + -0.6 + x2 = 0 + -0.6 Reorder the terms: 0.6 + -0.6 + 2.2x + x2 = 0 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + 2.2x + x2 = 0 + -0.6 2.2x + x2 = 0 + -0.6 Combine like terms: 0 + -0.6 = -0.6 2.2x + x2 = -0.6 The x term is 2.2x. Take half its coefficient (1.1). Square it (1.21) and add it to both sides. Add '1.21' to each side of the equation. 2.2x + 1.21 + x2 = -0.6 + 1.21 Reorder the terms: 1.21 + 2.2x + x2 = -0.6 + 1.21 Combine like terms: -0.6 + 1.21 = 0.61 1.21 + 2.2x + x2 = 0.61 Factor a perfect square on the left side: (x + 1.1)(x + 1.1) = 0.61 Calculate the square root of the right side: 0.781024968 Break this problem into two subproblems by setting (x + 1.1) equal to 0.781024968 and -0.781024968.Subproblem 1
x + 1.1 = 0.781024968 Simplifying x + 1.1 = 0.781024968 Reorder the terms: 1.1 + x = 0.781024968 Solving 1.1 + x = 0.781024968 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1' to each side of the equation. 1.1 + -1.1 + x = 0.781024968 + -1.1 Combine like terms: 1.1 + -1.1 = 0.0 0.0 + x = 0.781024968 + -1.1 x = 0.781024968 + -1.1 Combine like terms: 0.781024968 + -1.1 = -0.318975032 x = -0.318975032 Simplifying x = -0.318975032Subproblem 2
x + 1.1 = -0.781024968 Simplifying x + 1.1 = -0.781024968 Reorder the terms: 1.1 + x = -0.781024968 Solving 1.1 + x = -0.781024968 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1' to each side of the equation. 1.1 + -1.1 + x = -0.781024968 + -1.1 Combine like terms: 1.1 + -1.1 = 0.0 0.0 + x = -0.781024968 + -1.1 x = -0.781024968 + -1.1 Combine like terms: -0.781024968 + -1.1 = -1.881024968 x = -1.881024968 Simplifying x = -1.881024968Solution
The solution to the problem is based on the solutions from the subproblems. x = {-0.318975032, -1.881024968}
| 4v^2+31v-90= | | x^2+23= | | 25y=35 | | 6p^2-13p+2= | | 25y=3 | | -5x+4x=-1+5-x-4 | | 7m^2-3m= | | 3(2x+3)=-2(x+2)-3 | | 0=4.5c | | 5=7x+15-2x | | 28t=6(7t-6) | | 2+-15n=5(-3n+2) | | 5x-25=5x+24 | | 7b^2-6b= | | -10+0.25x=10 | | -10+0.25x=-5 | | 8+4k=-10+4k | | 4d+28=88 | | -3x^2+10x-7=0 | | 4u=37+4u | | -1550-7x=5 | | 7x^2+39x-70= | | 2n-8=7n+4+8 | | 4-(2x-3)=2(2x+1)+5 | | -2+4y=70 | | -2y=-2+x | | 7x^2-11x-6= | | 1*2+x=16 | | 3(x-1)=4x-8 | | p-2-6+12=4p-2 | | -2k+13=2m-3 | | 8b=6n-14 |